2015
DOI: 10.1016/j.ejmech.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Prospective performance evaluation of selected common virtual screening tools. Case study: Cyclooxygenase (COX) 1 and 2

Abstract: Computational methods can be applied in drug development for the identification of novel lead candidates, but also for the prediction of pharmacokinetic properties and potential adverse effects, thereby aiding to prioritize and identify the most promising compounds. In principle, several techniques are available for this purpose, however, which one is the most suitable for a specific research objective still requires further investigation. Within this study, the performance of several programs, representing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 71 publications
(125 reference statements)
1
21
0
Order By: Relevance
“…In particular, very recently novel chemical entities have been identified by different approaches such as: i) rational design providing novel scaffolds based on 4-phenylpyrimidine-2(1H)-thiones [8] and, indole based peptidomimetics [9], or ii) computational procedures providing novel and structurally unrelated COX-2 inhibitors [10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, very recently novel chemical entities have been identified by different approaches such as: i) rational design providing novel scaffolds based on 4-phenylpyrimidine-2(1H)-thiones [8] and, indole based peptidomimetics [9], or ii) computational procedures providing novel and structurally unrelated COX-2 inhibitors [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, a systematic and prospective investigation of the applicability of these tools for the different stages and tasks in drug development has not been accomplished so far. We already analyzed the suitability of different pharmacophore‐, shape‐, and 2D similarity‐based methods, and docking for cyclooxygenases (COX) 1 and 2 40. We applied COX as representative of classical enzymes that catalyze the production of specific endogenous molecules according to the physiological requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to that target class, we investigated CYP enzymes interacting with a large variety of exogenous molecules in this study. In the COX‐study, we observed large differences in the performance of these programs,40 suggesting the need of a critical selection of the screening method for performing in silico activity predictions. Compared to classical enzymes, xenobiotic metabolizing proteins have to fulfill a completely different biological function, and therefore also differ in their structural features.…”
Section: Introductionmentioning
confidence: 99%
“…To elaborate the virtual screening process for drug discovery, authors of [25,24] evaluated common virtual screening tool, which is used to identify novel bioactive molecules for cyclooxygenases-1 and -2 as representatives of classical enzymes [25] and to identify novel peroxisome proliferator-activated receptor (PPARγ) ligands [24]. PPARγ belongs to nuclear receptor class, and is a valuable drug target.…”
Section: Vs Assaymentioning
confidence: 99%